The response of the macaque tracheobronchial epithelium to acute ozone injury. A quantitative ultrastructural and autoradiographic study. - Wilson, D. W. (1984)
The tracheal epithelium of a variety of laboratory species is widely used as a model system in studies of epithelial biology and respiratory carcinogenesis. The purpose of this study was to evaluate the response of the tracheal epithelium to cytotoxic injury in a primate species that may have an epithelium more representative of that in man than smaller laboratory species. This study evaluated changes in the light-microscopic, surface, and ultrastructural appearance of the tracheobronchial epithelium of bonnet monkeys exposed for 3 or 7 days to 0.64 ppm ozone. Population densities, epithelial volumetric densities, and thymidine labeling indexes were determined for cells from posterior membranous and anterior cartilaginous trachea and mainstem bronchus. Ozone-induced epithelial changes were characterized by decreased numbers of ciliated cells, loss of cilia, and necrosis of ciliated cells. There were alterations in mucous (goblet) cell granules. There was an increase in extracellular space and focal epithelial stratification that was associated with increased numbers of small mucous granule cells and the presence of an epithelial cell type not seen in control animals (intermediate cells). There was an increase in cytoplasmic filaments and desmosomal attachments in basal cells, small mucous granule cells, and intermediate cells. Regional differences in lesion distribution were demonstrated by scanning electron microscopy. Longitudinal streaks of ciliary loss were evident in posterior membranous trachea, but ciliary loss in the ventral trachea was most prominent over the posterior border of the cartilaginous rings. The thymidine labeling index and numbers of necrotic ciliated cells were greater after 3 days than after 7 days of continuous exposure. Foci of stratification were often associated with increased numbers of labeled nuclei in the suprabasal region of the epithelium. The results of this study suggest that small mucous granule cells and intermediate cells are important participants in the repair of chemically injured airway epithelium; stratification and increased amounts of cytoplasmic filament bundles and desmosomal attachments, rather than being evidence of squamous metaplasia or dysplastic change, might be stereotypic responses of airway epithelium to injury; and the ciliated cell population becomes less susceptible to ozone-induced necrosis with continuing exposure.